Pengaruh Relaksasi Napas dalam Sebagai Intervensi Non Farmakologis terhadap Penurunan Kecemasan pada Ibu Hamil - Dewi, Novela Eka Candra; Jatmiko, Desinta Dwi; Fitrianingsih, Dina; Nisa', Dina Khoirun; Lestari, Dinda Dwi; Febrianti, Dini (Universitas Nurul Jadid, 2025)
The third trimester of pregnancy is often marked by heightened anxiety as mothers approach childbirth. Unmanaged anxiety may negatively affect both maternal psychological well-being and fetal health. This study aimed to evaluate the effectiveness of deep breathing relaxation in reducing anxiety among third-trimester pregnant women. A pre-experimental design with one-group pretest–posttest was applied to 24 eligible participants. The intervention consisted of deep breathing exercises conducted for two weeks, 2–3 times per week, each lasting 10–15 minutes. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS). Results revealed a decrease in mean anxiety scores from 11.12 (pretest) to 8.08 (posttest), with a mean reduction of 3.04 points. The Wilcoxon test showed a significant difference (p = 0.000, p < 0.05) between pre- and post-intervention scores. These findings confirm that deep breathing relaxation is effective in lowering anxiety during the third trimester of pregnancy. Practical implications highlight the importance of incorporating this technique into antenatal care programs, not only as a relaxation strategy but also as a structured component of maternal education and psychological support prior to delivery.